An evaluation of the organ procurement and transplantation network's expanded post-transplant performance metrics - Malamon, John S.; Ho, Bing; Jackson, Whitney E.; Saben, Jessica L.; Schold, Jesse D.; Pomposelli, James J.; Pomfret, Elizabeth A.; Kaplan, Bruce (Frontiers in Transplantation, 2023)
On July 14, 2022, the Organ Procurement and Transplantation Network's (OPTN) Membership and Professional Standards Committee (MPSC) approved bylaws including two new post-transplant performance evaluation metrics, the 90-day (90D) and 1-year conditional on the 90-day (1YC90D) graft survival hazard ratio (HR). These metrics have replaced the previous 1-year (1Y) unconditional, post-transplant graft survival HR and are used to nationally rank and identify programs for MPSC review. The MPSC's policies have major implications for all transplant programs, providers, and patients across the United States. Herein we show two significant limitations with the new evaluation criteria, arbitrary censoring periods and interdependence in the new performance metrics. We have demonstrated a strong and consistent inverse correlation between the new evaluation metrics, thus proving a lack of independence.Moreover, these two evaluation criteria are interdependent even at nominal HRs. Thus, the 90D cohort can be used to accurately predict whether the 1YC90D is above or below a given HR threshold. This could alter practice behaviors and the timing of patient event reporting, which may result in many unintended consequences related to clinical practice. Here we provide the first evidence that this new evaluation system will lead to a significant increase in the number of programs flagged for MPSC review. When this occurs, the cost of operating a transplant program will increase without a clear demonstration of an increased accuracy in identifying problematic programs.